Bimetallic palladium nickel nanoparticles anchored on carbon as high-performance electrocatalysts for oxygen reduction and formic acid oxidation reactions - Goswami, Chiranjita; Saikia, Himadri; Tada, Kohei; Tanaka, Shingo; Sudarsanam, Putla; Bhargava, Suresh K.; Bharali, Pankaj (ACS Applied Energy Materials, 2020)
{Herein, we report the synthesis of carbon-supported palladium-nickel electrocatalysts (ECs) (Pd4-xNix/C ECs
Keywords: electrocatalysts; Formic Acid Oxidation; fuel cells; oxygen reduction reaction; palladium-nickel alloy

Insights from a pan India Sero-epidemiological survey (Phenome-India Cohort) for SARS-CoV2 - Naushin, Salwa; Sardana, Viren; Ujjainiya, Rajat; Bhatheja, Nitin; Kutum, Rintu; Bhaskar, Akash Kumar; Pradhan, Shalini; Prakash, Satyartha; Khan, Raju; Rawat, Birendra Singh; Tallapaka, Karthik Bharadwaj; Anumalla, Mahesh; et al. (eLife, 2021)
To understand the spread of SARS-CoV2, in August and September 2020, the Council of Scientific and Industrial Research (India) conducted a serosurvey across its constituent laboratories and centers across India. Of 10,427 volunteers, 1058 (10.14%) tested positive for SARS-CoV2 anti-nucleocapsid (anti-NC) antibodies, 95% of which had surrogate neutralization activity. Three-fourth of these recalled no symptoms. Repeat serology tests at 3 (n = 607) and 6 (n = 175) months showed stable anti-NC antibodies but declining neutralization activity. Local seropositivity was higher in densely populated cities and was inversely correlated with a 30-day change in regional test positivity rates (TPRs). Regional seropositivity above 10% was associated with declining TPR. Personal factors associated with higher odds of seropositivity were high-exposure work (odds ratio, 95% confidence interval, p value: 2.23, 1.92-2.59, <0.0001), use of public transport (1.79, 1.43-2.24, <0.0001), not smoking (1.52, 1.16-1.99, 0.0257), non-vegetarian diet (1.67, 1.41-1.99, <0.0001), and B blood group (1.36, 1.15-1.61, 0.001).

Machine learning-based approach to determine infection status in recipients of BBV152 (Covaxin) whole-virion inactivated SARS-CoV-2 vaccine for serological surveys - Singh, Prateek; Ujjainiya, Rajat; Prakash, Satyartha; Naushin, Salwa; Sardana, Viren; Bhatheja, Nitin; Singh, Ajay Pratap; Barman, Joydeb; Kumar, Kartik; Gayali, Saurabh; Khan, Raju; Rawat, Birendra Singh; et al. (Computers in Biology and Medicine, 2022)
Data science has been an invaluable part of the COVID-19 pandemic response with multiple applications, ranging from tracking viral evolution to understanding the vaccine effectiveness. Asymptomatic breakthrough infections have been a major problem in assessing vaccine effectiveness in populations globally. Serological discrimination of vaccine response from infection has so far been limited to Spike protein vaccines since whole virion vaccines generate antibodies against all the viral proteins. Here, we show how a statistical and machine learning (ML) based approach can be used to discriminate between SARS-CoV-2 infection and immune response to an inactivated whole virion vaccine (BBV152, Covaxin). For this, we assessed serial data on antibodies against Spike and Nucleocapsid antigens, along with age, sex, number of doses taken, and days since last dose, for 1823 Covaxin recipients. An ensemble ML model, incorporating a consensus clustering approach alongside the support vector machine model, was built on 1063 samples where reliable qualifying data existed, and then applied to the entire dataset. Of 1448 self-reported negative subjects, our ensemble ML model classified 724 to be infected. For method validation, we determined the relative ability of a random subset of samples to neutralize Delta versus wild-type strain using a surrogate neutralization assay. We worked on the premise that antibodies generated by a whole virion vaccine would neutralize wild type more efficiently than delta strain. In 100 of 156 samples, where ML prediction differed from self-reported uninfected status, neutralization against Delta strain was more effective, indicating infection. We found 71.8% subjects predicted to be infected during the surge, which is concordant with the percentage of sequences classified as Delta (75.6%-80.2%) over the same period. Our approach will help in real-world vaccine effectiveness assessments where whole virion vaccines are commonly used.
Keywords: BBV152; Covaxin; COVID-19; Ensemble methods; Infection; machine learning; SARS-CoV-2

Durable and stable bifunctional Co3O4-based nanocatalyst for oxygen reduction/evolution reactions - Chutia, Bhugendra; Chetry, Rashmi; Rao, Komateedi N.; Singh, Nittan; Sudarsanam, Putla; Bharali, Pankaj (ACS Applied Nano Materials, 2024)
The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are recognized as the core reaction processes in regenerative energy storage and conversion systems. The design of cost-effective and high-performance bifunctional ORR/OER electrocatalysts (ECs) is very important for their substantial commercialization. Herein, sponge-like Co3O4 nanoparticles anchored on carbon (Sp-Co3O4/C) are successfully fabricated by a facile two-step solvothermal strategy for ORR/OER in an alkaline electrolyte. The Sp-Co3O4/C EC exhibits promising bifunctional ORR/OER activity with ORR onset potential (E onset = 0.88 V vs RHE), half-wave potential (E (1/2) = 0.75 V), limiting current density (j = -6.60 mA cm(-2)), OER onset potential (E-onset = 1.26 V), and OER overpotential for 10% energy conversion (eta(10) = 0.38 V) in 0.1 M KOH. It demonstrates a significantly lower reversibility index (Delta E = E- j10 - E 1/2 = 0.86 V), comparable to standard Pt/C and RuO2 ECs. The superior ORR/OER performances of Sp-Co3O4/C EC can be ascribed to the synergistic contribution of a high electrochemically active surface area (48.33 m(2) g(-1)), BET surface area (131 m(2) g(-1)), the rich interfacial structure of the crystal facets (111), (220), and (311), and the abundant oxygen vacancies in the sponge-like morphology. Besides the methanol tolerance, accelerated durability and chronoamperometric test established excellent durability and stability in the electrocatalytic operation. This work offers insight into the development of high-performance ORR/OER ECs. [GRAPHICS]
Keywords: bifunctional; fuel cell; interface; oxygen evolution; oxygen reduction; Oxygen vacancy; Sp-Co3O4/C; sponge-like morphology

Efficient glycolysis of used PET bottles into a high-quality valuable monomer using a shape-engineered MnO nanocatalyst - Swapna, Bhattu; Singh, Nittan; Patowary, Suranjana; Bharali, Pankaj; Madras, Giridhar; Sudarsanam, Putla (CATALYSIS SCIENCE & TECHNOLOGY, 2024)
Keywords: Catalyst; kinetics; Nanorods; Oxidation; Oxides; POLY(ETHYLENE-TEREPHTHALATE); WASTE